Oxidant/Antioxidant Balance in Animal Nutrition and Health: The Role of Protein Oxidation - Celi, Pietro; Gabai, Gianfranco (Frontiers in Veterinary Science, 2015)
This review examines the role that oxidative stress, and protein oxidation in particular, plays in nutrition, metabolism and health of farm animals. The route by which redox homeostasis is involved in some important physiological functions and the implications of the impairment of oxidative status on animal health and diseases is also examined. Proteins have various and, at the same time, unique biological functions and their oxidation can result in structural changes and various functional modifications. Protein oxidation seems to be involved in pathological conditions such as respiratory diseases and parasitic infection; however some studies also suggest that protein oxidation plays a crucial role in the regulation of important physiological functions such as reproduction, nutrition, metabolism, lactation, gut health and neonatal physiology. As the characterization of the mechanisms by which oxidative stress may influence metabolism and health is attracting considerable scientific interest, the aim of this review is to present veterinary scientists and clinicians with various aspects of oxidative damage to proteins.